Irrigated composite liner designs for fast hydration and prevention of thermal desiccation of geosynthetics clay liners. Issue 6 (December 2020) - Yu, Bowei; El-Zein, Abbas
Abstract: In composite liners made of geomembrane (GMB)- geosynthetics clay liners (GCLs), maintaining bentonite in the GCL in a suitably hydrated state is critical for their performance. Hydration of GCL from subsoil, following industry best practice, is time consuming and conditional on suitable water chemistry in subsoil. In addition, under thermal gradients, dehydration occurs, with moisture migrating downwards to the subsoil, leading to the development of cracks in the bentonite and hence loss of performance. Two novel ideas are proposed in this paper, namely hydration of GCLs by artificial irrigation and hydraulic separation of the liner system from the underlying subsoil. Three new composite liner designs allowing for actively irrigating a geosynthetic clay liner (GCL) through a geocomposite layer were investigated. In two of the three designs, the hydraulic connection between the GCL and the subsoil was broken by placing an additional GMB between them. The new designs were tested in column experiments under 20 kPa overburden pressure and temperatures of up to 78 °C applied to the top of the liner. The performances of the new designs were compared to that of a standard GCL-GMB design where GCL was allowed to hydrate from a well-graded sandy subsoil. Three scenarios for the staging of hydration and thermal load application were investigated. Under active hydration of the composite liners, it took less than 14 days for the GCLs to reach a gravimetric water content ω of 110–130%, compared to 49 days taken to reach ω~95% under hydration from the subsoil. GCLs in the new designs in which the hydraulic connection with the subsoil was broken, remained well-hydrated (ω>100%) after 14 days of heating and no cracks appeared in the bentonite. On the other hand, the GCL in the conventional design experienced severe desiccation under the same conditions. The new designs hence offer a viable solution to the problem of slow hydration and/or thermal desiccation of GCLs.